The Dynamic Response Process to Conflicting Institutional Demands in MNC Subsidiaries: An Inductive Study in the Sub‐Saharan African E‐Commerce Sector. (February 2017) - Holm, Alison E.; Decreton, Benoit; Nell, Phillip C.; Klopf, Patricia
Abstract : Research Summary: How do subsidiary managers react when their headquarters' managers make requests that conflict with the local environment in which the subsidiary operates? Using data from a subsidiary based in Sub‐Saharan Africa and headquartered in Europe, we show that subsidiary managers need more time than usually expected to react to headquarters' demands. Subsidiary managers sometimes postpone or test headquarters' demands before deciding how to respond to them. In addition, subsidiary managers can implement headquarters' demands in ways that do not fit the expectations from the headquarters or local actors (e.g., customers and suppliers), thus resulting in additional delays. Headquarters managers must be aware that implementation can take longer than they anticipate, particularly for subsidiaries located in environments that differ substantially from the environment of the headquarters. Managerial summary: In this article, we examine responses to the conflicting institutional demands faced by an e‐commerce subsidiary located in Sub‐Saharan Africa and headquartered in Europe. Following an inductive approach, we gathered data from a six‐month participant‐observation study and interviews with local managers. Our findings show that the subsidiary managers responded to conflicting institutional demands in a dynamic way, taking one response after the other. In some cases, the subsidiary managers responded in a way that they thought would be satisfactory, but subsequent pressures from their headquarters or their local environment pushed them to adopt a new response. In other cases, the subsidiary managers intentionally adopted responses knowing they would (have to) adopt another response later in the process. Copyright © 2016 John Wiley & Sons, Ltd.